ANALYSIS OF MUI FATWA NO. 83 OF 2023 CONCERNING THE BOYCOTT OF PRODUCTS AFFILIATED WITH ISRAEL BASED ON THE THEORY OF SADD AZ- ZARI'AH - Isratul Marfirah (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The dynamics of the conflict between Palestine and Israel, made the Indonesian Ulema Council issue MUI Fatwa No. 83 of 2023 concerning the Prohibition of Transactions and the Use of Products Affiliated with Israel, which initially the law of transaction activities and the use of products is permissible. Therefore, this study aims to analyse MUI Fatwa No. 83 of 2023 concerning the prohibition of transactions of products affiliated with Israel from the perspective of saddudzari'ah. The type of research conducted is library research. The method used is a qualitative method with a normative legal approach. The primary data source in this study is MUI Fatwa No. 83 of 2023 concerning the Law of Support for the Struggle for Palestine. While secondary data is taken from books or articles related to the title of the study. Then the data is analysed using data analysis methods or techniques that involve dissecting the text or contents of the book. This study concludes two things. First, the legal basis used by the MUI in determining MUI Fatwa No. 83 on the law on the Palestinian struggle, according to the objectives and contents of the fatwa. Second, the saddudzariah review of MUI Fatwa No. 83 of 2023 concerning the Law on Support for the Palestinian Struggle changes the law on transactions and the use of products affiliated with Israel, when viewed from the pillars of sadd saddudzari'ah, namely on actions or actions that apply so that intermediaries to something, in MUI Fatwa No. 83 of 2023, namely initially the law on transactions and the use of products affiliated with Israel was permissible or allowed to be forbidden. Because there is a strong suspicion that it brings damage, namely, it can support Israeli aggression against Palestine either directly or indirectly.